PENGEMBANGAN BAHAN AJAR ELEMEN GEOMETRI TOPIK LINGKARAN BERBASIS ETNOMATEMATIKA PADA SISTEM LODOK DI MASYARAKAT MANGGARAI - Jehurung, Paulus; Dominikus, Wara Sabon; Wulakada, Hamza H. (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study stems from the challenges students face in understanding geometry concepts, particularly circles, due to abstract instruction and limited real-life context. To address this issue, mathematics teaching materials were developed based on ethnomathematics by integrating the Lodok system a traditional radial land division system practiced by the Manggarai people of East Nusa Tenggara as a culturally rich and geometrically relevant local context. The study aimed to identify geometric concepts embedded in the Lodok system and to develop teaching materials that integrate these local wisdom elements to enhance students’ conceptual understanding and character development. The research employed the 4D development model (Define, Design, Develop, Disseminate) and a qualitative approach. The Define stage involved literature review, field observation, and interviews with traditional leaders to formulate learning objectives and develop the material framework. The Design stage produced an initial draft of the Lodok-based teaching material, validated by subject matter experts and education practitioners. The Develop stage included a trial with 32 eighth-grade students at SMP Negeri 12 Kupang to assess practicality and preliminary effectiveness, while the Disseminate stage was conducted with 28 students at SMP Negeri 1 Cibal, a culturally representative Lodok site, to evaluate final effectiveness. Validation results confirmed the teaching material was highly appropriate; practicality tests indicated it was user-friendly, engaging, and aided conceptual understanding; and effectiveness tests revealed that over 85% of students achieved mastery in circle-related concepts, which were linked to Lodok components such as langang, banta, cicing, and moso. Beyond cognitive gains, the integration of Lodok also strengthened student character, particularly in justice, cooperation, and cultural appreciation. The study concludes that the developed material is valid, practical, and effective, and recommends the adoption of ethnomathematics approaches in other culturally rich regions to bridge formal mathematics with students’ lived realities. ABSTRAKPenelitian ini dilatarbelakangi oleh kesulitan siswa dalam memahami konsep geometri, khususnya lingkaran, akibat pembelajaran yang abstrak dan minim konteks nyata. Untuk menjawab tantangan ini, peneliti mengembangkan bahan ajar matematika berbasis etnomatematika dengan mengangkat sistem Lodok (pembagian lahan khas masyarakat Manggarai, Nusa Tenggara Timur) sebagai konteks lokal yang sarat nilai geometris dan budaya. Fokus permasalahannya adalah bagaimana mengembangkan bahan ajar elemen Geometri Topik Lingkaran berbasis Etnomatematika pada sistem Lodok di masyarakat Manggarai. Tujuan penelitian ini adalah mengembangkan bahan ajar elemen Geometri Topik Lingkaran berbasis Etnomatematika pada sistem Lodok di masyarakat Manggarai guna meningkatkan pemahaman dan karakter siswa. Metode yang digunakan adalah model pengembangan 4D (Define, Design, Develop, Disseminate) serta pendekatan kualitatif. Tahap define meliputi studi literatur, observasi, dan untuk merumuskan tujuan dan kisi-kisi bahan ajar. Tahap design menghasilkan draf awal bahan ajar yang divalidasi oleh ahli dan praktisi. Tahap develop dilakukan melalui uji coba pada 32 siswa SMP Negeri 12 Kupang, sedangkan tahap disseminate diterapkan pada 28 siswa SMP Negeri 1 Cibal untuk menilai efektivitas di lingkungan budaya Lodok. Hasil validasi menunjukkan bahan ajar sangat layak, uji kepraktisan menunjukkan bahan ajar praktis atau mudah digunakan dan membantu pemahaman konsep lingkaran yang diintegrasikan dengan unsur Lodok seperti langang, banta, cicing, dan moso, sementara uji efektivitas menunjukkan peningkatan pemahaman 96,87 % pada tahap uji coba dan 100 % pada tahap diseminasi. Selain peningkatan kognitif, integrasi sistem Lodok juga menguatkan karakter siswa, terutama nilai keadilan, gotong royong, dan penghargaan budaya lokal. Simpulan penelitian ini menunjukkan bahwa bahan ajar berbasis Etnomatematika yang dikembangkan layak, praktis, dan efektif, serta merekomendasikan pendekatan Etnomatematika di daerah lain untuk menjembatani matematika formal dengan realitas budaya lokal.